A preparation method of an electrochemical sensor based on a composite metal organic framework material and application of the electrochemical sensor in detecting chloramphenicol

By preparing a ZIF-67/PBA composite material modified electrode, the problems of high instrument cost and insufficient sensitivity in existing chloramphenicol detection were solved, and chloramphenicol detection with high sensitivity and high accuracy was achieved.

CN118311111BInactive Publication Date: 2025-01-14JIANGHAN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410500603.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for detecting chloramphenicol suffer from problems such as high equipment costs, complex operation, and insufficient sensitivity.

Method used

ZIF-67 metal-organic framework material was prepared by crystal growth method, and a Prussian blue analogue was compounded on it to prepare ZIF-67/PBA composite material, which was then used to modify the surface of glassy carbon electrode for the fabrication of electrochemical sensors.

Benefits of technology

It achieves high sensitivity and high accuracy in the detection of chloramphenicol. The instrument is inexpensive, portable, easy to operate, and has a detection limit as low as 5.1 μM.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118311111B_ABST
    Figure CN118311111B_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an electrochemical sensor based on a composite metal-organic framework material and application of the electrochemical sensor in detecting chloramphenicol. The electrochemical sensor is prepared by modifying an electrode with a composite material of a metal-organic framework material and a Prussian blue analogue. ZIF-67 / PBA has excellent electrocatalytic activity and can catalyze CAP reduction to generate a current response. Different electrochemical responses are generated based on different concentrations of CAP. According to the linear relationship between CAP concentration and current intensity, high-sensitivity and high-selectivity electrochemical detection of the antibiotic drug chloramphenicol can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical analysis, and in particular to a method for preparing an electrochemical sensor based on a composite metal organic framework material and application of the electrochemical sensor in detecting chloramphenicol. Background Art

[0002] Chloramphenicol (CAP) is a broad-spectrum antibiotic widely used to treat various infectious diseases caused by Gram-positive and Gram-negative bacteria. However, excessive residues of CAP in food or animals may cause adverse side effects in humans, including leukemia, gray baby syndrome, and aplastic anemia. Therefore, the United States, the European Union, China, Switzerland and other countries and regions have banned the use of CAP in agriculture and food animal production. With the increase of antibiotic drug contaminants in the global system, the development of sensitive and accurate methods to monitor and control CAP is of great significance for reducing environmental pollution and maintaining human health. Compared with traditional detection methods, electrochemical detection methods have the outstanding advantages of high sensitivity and good selectivity, low cost, and simple instrument operation, so they show great potential in the field of sensor detection.

[0003] In order to improve the quality of the sensor, a high-performance electrocatalyst is prepared for electrode modification to enhance the rate of the redox reaction at the electrode interface, generate an amplified and stable current signal, and greatly improve the detection performance of the sensor, thereby achieving high-sensitivity and high-accuracy detection. Based on this, this application is proposed. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing an electrochemical sensor based on a composite metal organic framework material and the application of the electrochemical sensor in the detection of chloramphenicol, so as to solve the problems of high instrument and equipment cost, complex operation and insufficient sensitivity in the existing detection method for chloramphenicol detection.

[0005] The present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an electrochemical sensor based on a composite metal organic framework material, comprising the following steps:

[0007] S1. Preparation of ZIF-67 metal organic framework material by crystal growth method;

[0008] S2, compounding a Prussian blue analog on a ZIF-67 metal organic framework material to obtain an electrode modified composite material;

[0009] S3. Dispersing the electrode modified composite material in water to obtain a suspension, and then drop-coating it on the surface of the glassy carbon electrode to obtain the electrochemical sensor.

[0010] Furthermore, step S1 is specifically as follows: ultrasonically dissolving a certain amount of cobalt nitrate hexahydrate and dimethylimidazole in a certain amount of methanol respectively; then quickly injecting the methanol solution of cobalt nitrate into the dimethylimidazole solution, reacting at room temperature for a period of time, collecting the precipitate by centrifugation, washing and drying, and obtaining the ZIF-67 metal organic framework material.

[0011] Furthermore, step S2 is specifically as follows: weigh a certain amount of the ZIF-67 metal organic framework material and potassium ferrocyanide solid prepared in step S1, ultrasonically disperse them in a mixed solvent of ethanol and water, stir at room temperature for a period of time, centrifuge and collect and wash, and the obtained solid is the electrode modified composite material.

[0012] Furthermore, in step S1, the mass ratio of cobalt nitrate hexahydrate to dimethylimidazole is 0.58:0.65, and the reaction time is 2 hours.

[0013] Furthermore, in step S2, the mass ratio of the ZIF-67 metal organic framework material to potassium ferrocyanide is 2:1, the volume ratio of ethanol to water is 1:1, and the reaction time is 4 hours.

[0014] Furthermore, the concentration of the electrode-modified composite material in the suspension is 2 mg / mL, and the modification amount of the electrode-modified composite material in the electrochemical sensor is 1 to 8 μL, preferably 5 μL.

[0015] The present invention also provides application of the electrochemical sensor prepared by the preparation method in detecting the antibiotic drug chloramphenicol.

[0016] In the electrochemical sensor, the electrode is modified by a composite material of a metal organic framework material and a Prussian blue analogue. ZIF-67 / PBA has excellent electrocatalytic activity and can catalyze the reduction of CAP to produce a current response. Different electrochemical responses are produced based on different CAP concentrations. According to the linear relationship between CAP concentration and current intensity, high-sensitivity and high-selectivity electrochemical detection of the antibiotic drug chloramphenicol can be achieved.

[0017] Furthermore, the detection method is: using an electrochemical sensor as a working electrode, a calomel electrode as a reference electrode, and a platinum electrode as a counter electrode, immersing the electrochemical sensor in an acetic acid-sodium acetate buffer solution containing chloramphenicol, performing a differential pulse voltammetry test, measuring the current response under different chloramphenicol concentrations, drawing a standard curve of current intensity and chloramphenicol concentration, and analyzing to obtain the chloramphenicol content, with a detection limit as low as 5.1 μM.

[0018] Furthermore, the pH of the acetic acid-sodium acetate buffer solution is 3.4-5.2, preferably 4.

[0019] Furthermore, the DPV scanning parameters are: Init E is -0.3V, Final E is -0.9V, Incr E is 0.004V, Amplitude is 0.05V, Pulse Width is 0.05s, Sampling Width is 0.0167s, Pulse Period is 0.5s, and Quiet Time is 2s.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] (1) The preparation of ZIF-67 / PBA composites by growing PBA on the surface of ZIF-67 can significantly improve the catalytic activity of a single material. The synthesis process is simple and easy, can be operated at room temperature, and has low cost.

[0022] (2) The prepared ZIF-67 / PBA composite material was used for electrode modification to obtain an electrochemical sensor based on the ZIF-67 / PBA composite material with good catalytic performance and stable response signal.

[0023] (3) The electrochemical analysis method of the present invention realizes the detection of chloramphenicol. The instrument used is cheap and portable. The preparation method of the sensor is simple and easy. The signal response is fast and has high sensitivity. The detection limit is as low as 5.1 μM.

[0024] (4) The electrochemical analysis method of the present invention can be used for actual sample detection, and the design idea of ​​the preparation method of the sensor provides great help for the development of similar types of sensors for the detection of other target analytes, and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 A schematic diagram of the process of preparing the electrochemical sensor and the application detection process of the present invention;

[0027] Figure 2 The scanning electron microscope image and the corresponding element distribution map of the ZIF-67 / PBA composite material in Example 1 of the present invention;

[0028] Figure 3 Cyclic voltammograms and electrochemical impedance spectroscopy diagrams of electrodes modified with different materials in the present invention;

[0029] Figure 4 The current response diagrams and corresponding current values ​​of electrodes modified with different materials in the present invention to chloramphenicol catalysis;

[0030] Figure 5 It is a current response diagram and a corresponding linear diagram of the sensor detecting CAP in the application embodiment of the present invention;

[0031] Figure 6 This is a current response diagram of the sensor detecting CAP under different material modification amounts in the present invention;

[0032] Figure 7 This is the current response diagram of the sensor detecting CAP under different pH conditions in the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention provides a method for preparing an electrochemical sensor based on a composite metal organic framework material, comprising the following steps:

[0035] S1. Preparation of ZIF-67 metal organic framework material by crystal growth method;

[0036] S2, compounding a Prussian blue analog on a metal organic framework to obtain an electrode modified composite material;

[0037] S3. Dispersing the electrode modified composite material in water to obtain a suspension, and then drop-coating it on the surface of the glassy carbon electrode to obtain the electrochemical sensor.

[0038] In a specific embodiment, step S1 is specifically as follows: a certain amount of cobalt nitrate hexahydrate and dimethylimidazole are ultrasonically dissolved in a certain amount of methanol; then the methanol solution of cobalt nitrate is quickly injected into the dimethylimidazole solution, reacted at room temperature for a period of time, centrifuged to collect the precipitate, washed and dried to obtain the ZIF-67 metal organic framework material. The mass ratio of cobalt nitrate hexahydrate to dimethylimidazole is 0.58:0.65, and the reaction time is 2 hours.

[0039] In a specific embodiment, step S2 is specifically as follows: weigh a certain amount of ZIF-67 metal organic framework material and potassium ferrocyanide solid prepared in step S1, ultrasonically disperse them in a mixed solvent of ethanol and water, stir at room temperature for a period of time, centrifuge and collect and wash, and the obtained solid is the electrode modified composite material. Wherein, the mass ratio of ZIF-67 metal organic framework material and potassium ferrocyanide is 2:1, the volume ratio of ethanol and water is 1:1, and the reaction time is 4 hours.

[0040] In a specific embodiment, the concentration of the electrode-modified composite material in the suspension is 2 mg / mL, and the modification amount of the electrode-modified composite material in the electrochemical sensor is 1 to 8 μL, preferably 5 μL.

[0041] The present invention also provides the use of the electrochemical sensor prepared above in detecting the antibiotic drug chloramphenicol.

[0042] The detection method comprises the following steps: using an electrochemical sensor as a working electrode, a calomel electrode as a reference electrode, and a platinum electrode as a counter electrode, immersing the electrochemical sensor in an acetic acid-sodium acetate buffer solution containing chloramphenicol, performing a differential pulse voltammetry test, measuring the current response under different chloramphenicol concentrations, drawing a standard curve of current intensity and chloramphenicol concentration, analyzing and obtaining the chloramphenicol content, and the detection limit is as low as 5.1 μM.

[0043] The pH of the acetic acid-sodium acetate buffer solution is 3.4-5.2, preferably 4.

[0044] DPV scanning parameters: Init E is -0.3V, Final E is -0.9V, IncrE is 0.004V, Amplitude is 0.05V, Pulse Width is 0.05s, SamplingWidth is 0.0167s, Pulse Period is 0.5s, and Quiet Time is 2s.

[0045] The present invention will be further described below by means of specific embodiments:

[0046] [Example 1]

[0047] The process of preparing the electrochemical sensor in this embodiment is as follows:

[0048] (1) 0.58 g Co(NO3)2·6H2O and 0.65 g dimethylimidazole were dissolved in 20 mL methanol, respectively. The methanol solution of Co(NO3)2 was then quickly injected into the dimethylimidazole solution. The mixture was reacted at room temperature for about 2 hours. The precipitate was collected by centrifugation and washed three times with methanol and water, respectively, and dried in a vacuum drying oven to obtain the metal organic framework material ZIF-67.

[0049] (2) Weigh 40 mg of ZIF-67 prepared in step (1) and 20 mg of potassium ferricyanide (K3[Fe(CN)6]) solid, ultrasonically disperse them in a mixed solvent of 20 mL of ethanol and water (volume ratio of 1:1), stir at room temperature for 4 hours, collect and wash the resulting solid by centrifugation to obtain a ZIF-67 / PBA composite material;

[0050] (3) Weigh 2 mg of ZIF-67 / PBA composite material and ultrasonically disperse it in 1 mL of water to prepare a 2 mg / mL suspension; polish the glassy carbon electrode (GCE) with 0.05 μm alumina, and ultrasonically clean it with water, ethanol, and water respectively. After drying, 5 μL of ZIF-67 / PBA composite material suspension is dropwise coated on the electrode surface and dried at room temperature to prepare an electrochemical sensor.

[0051] [Examples 2 to 6]

[0052] The modification amount of the ZIF-67 / PBA composite material in step (3) in each embodiment was 1 μL, 3 μL, 6 μL, 7 μL, and 8 μL, respectively, and the remaining steps were the same as in Example 1.

[0053] [Comparative Example 1]

[0054] (1) 0.58 g Co(NO3)2·6H2O and 0.65 g dimethylimidazole were dissolved in 20 mL methanol, respectively. The methanol solution of Co(NO3)2 was then quickly injected into the dimethylimidazole solution. The mixture was reacted at room temperature for about 2 hours. The precipitate was collected by centrifugation and washed three times with methanol and water, respectively, and dried in a vacuum drying oven to obtain the metal organic framework material ZIF-67.

[0055] (2) Weigh 2 mg of ZIF-67 material and ultrasonically disperse it in 1 mL of water to prepare a 2 mg / mL suspension; polish the glassy carbon electrode (GCE) with 0.05 μm alumina, and ultrasonically clean it with water, ethanol, and water respectively. After drying, 5 μL of the ZIF-67 material suspension was drop-coated on the electrode surface to obtain a ZIF-67 material modified electrode.

[0056] The ZIF-67 / PBA composite material prepared in Example 1 was subjected to scanning electron microscopy analysis and EDS elemental analysis. The results are shown in Figure 2 , showing that it is in the shape of a rhombic dodecahedron, with the four elements C, N, Co, and Fe evenly distributed.

[0057] The electrochemical sensor prepared in Example 1, the electrode modified with ZIF-67 material prepared in Comparative Example 1, and the unmodified glassy carbon electrode were immersed in 5 mM [Fe(CN)6] 3- / 4- Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed in the solution. Figure 3 As shown in the figure, compared with ZIF-67 / GCE, ZIF-67 / PBA / GCE has a stronger current response and a smaller charge transfer impedance, indicating that the growth of PBA helps to improve the conductivity of ZIF-67 and the ZIF-67 / PBA composite material has better electrochemical activity.

[0058] The ZIF-67 / PBA / GCE sensor obtained in Example 1, the ZIF-67 / GCE of Comparative Example 1, and the unmodified GCE were used as working electrodes, a saturated calomel electrode was used as a reference electrode, a platinum electrode was used as a counter electrode, and an acetic acid-sodium acetate buffer solution containing 200 μM CAP was used as an electrolyte solution to perform CV tests. The results are shown in FIG. Figure 4 As shown in the CV scan, CAP has two reduction peaks (R1, R2) and one oxidation peak (O1). Compared with GCE and ZIF-67 / GCE, ZIF-67 / PBA / GCE exhibits better electrocatalytic ability for CAP, and the peak current increases by 7.08 μA and 6.28 μA, respectively.

[0059] [Application Example]

[0060] The electrochemical sensor prepared in Example 1 was used as the working electrode, the calomel electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The electrochemical sensor was immersed in an acetic acid-sodium acetate buffer solution (pH = 4) containing chloramphenicol, and a differential pulse voltammetry test was performed to measure the current response under different chloramphenicol concentrations. Figure 5 As shown in the figure, the concentrations of CAP are 6.25, 12.5, 25, 50, 100, 150, and 200 μM, respectively. A standard curve of current intensity and chloramphenicol concentration is drawn. The current response increases with the increase of CAP concentration, and the corresponding linear relationship is i pc =-0.02c-0.84. The content of chloramphenicol in the sample to be tested can be analyzed according to the standard curve. The detection limit of this detection method is as low as 5.1 μM.

[0061] Among them, the DPV scanning parameters are: Init E is -0.3V, Final E is -0.9V, Incr E is 0.004V, Amplitude is 0.05V, Pulse Width is 0.05s, Sampling Width is 0.0167s, Pulse Period is 0.5s, and Quiet Time is 2s.

[0062] The electrochemical sensors prepared in Examples 1 to 6 were used to detect CAP. The sensors were immersed in a HAc-NaAc buffer solution (pH = 4) containing 200 μM CAP as working electrodes for DPV testing. The results are shown in Figure 6As shown, with the increase of the amount of material modification, the DPV reduction peak (R1) current first increases and then decreases, so the optimal modification amount is selected as 5 μL, and Example 1 has the best effect.

[0063] The electrochemical sensor prepared in Example 1 was subjected to DPV test in HAc-NaAc buffer solutions of different pH values ​​(pH values ​​were 3.4, 4.0, 4.6, 5.0, and 5.2, respectively) containing 200 μM CAP. Figure 7 As shown, with the increase of the pH of the buffer solution, the DPV reduction peak (R1) current first increases and then decreases, so the optimal pH is 4.

[0064] The electrochemical sensor designed by the present invention based on the metal organic framework and the Prussian blue analog composite material has the advantages of high sensitivity and fast response, and can be used to detect the antibiotic drug chloramphenicol. The detection method has good reproducibility, a wide detection range, high sensitivity and good stability. The design ideas provided by the present invention may provide great help for the development of ultra-sensitive electrochemical sensors for identifying other target analytes.

[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of an electrochemical sensor based on a composite metal organic framework material in detecting the antibiotic drug chloramphenicol, characterized in that: The detection method is as follows: using an electrochemical sensor as a working electrode, a calomel electrode as a reference electrode, and a platinum electrode as a counter electrode, immersing the electrochemical sensor in an acetic acid-sodium acetate buffer solution containing chloramphenicol, performing a differential pulse voltammetry test, measuring the current response under different chloramphenicol concentrations, and drawing a standard curve of current intensity and chloramphenicol concentration. The content of chloramphenicol is analyzed, and the detection limit is as low as 5.1 μM. The electrochemical sensor is prepared by the following steps: S1. Preparation of ZIF-67 metal organic framework material by crystal growth method: a certain amount of cobalt nitrate hexahydrate and dimethylimidazole are ultrasonically dissolved in a certain amount of methanol respectively; the methanol solution of cobalt nitrate is then quickly injected into the dimethylimidazole solution, reacted at room temperature for a period of time, centrifuged to collect the precipitate, washed and dried to obtain the ZIF-67 metal organic framework material; S2, weighing a certain amount of the ZIF-67 metal organic framework material and potassium ferrocyanide solid prepared in step S1, ultrasonically dispersing them in a mixed solvent of ethanol and water, stirring at room temperature for a period of time, centrifugally collecting and washing, to obtain an electrode modified composite material; the mass ratio of the ZIF-67 metal organic framework material to potassium ferrocyanide is 2:1, the volume ratio of ethanol to water is 1:1, and the reaction time is 4 hours; S3. Dispersing the electrode modified composite material in water to obtain a suspension, and then drop-coating it on the surface of the glassy carbon electrode to obtain the electrochemical sensor.

2. The use according to claim 1, wherein in step S1, the mass ratio of cobalt nitrate hexahydrate to dimethylimidazole is 0.58:0.65, and the reaction time is 2 hours.

3. The use according to claim 1, characterized in that: The concentration of the electrode modified composite material in the suspension is 2 mg / mL, and the modification amount of the electrode modified composite material in the electrochemical sensor is 1 to 8 μL.

4. The use according to claim 3, characterized in that: The modification amount of the electrode modified composite material in the electrochemical sensor is 5 μL.

5. The use according to claim 1, characterized in that: The pH of the acetic acid-sodium acetate buffer solution is 3.4-5.

2.

6. The use according to claim 5, characterized in that: The pH of the acetic acid-sodium acetate buffer solution is 4.

7. The use according to claim 1, characterized in that: DPV scanning parameters: Init E is -0.3V, Final E is -0.9V, Incr E is 0.004V, Amplitude is 0.05V, Pulse Width is 0.05s, Sampling Width is 0.0167s, Pulse Period is 0.5s, and Quiet Time is 2s.

Citation Information

Patent Citations

  • Method for detecting chloramphenicol by utilizing ultrasonic stripping porous carbon modified electrode

    CN106324056A